Relational Arts-Based Teaching and Learning in Higher Education: Engaging the Mind, Body, and Soul of Child and Youth Care Students - Brandson, Ashley; Chambers, Elisha; Evenson, Mekenna; Gladue, Victoria; Hein, Brenna; Laurie, Ryanna; O’Keefe, Turner; Slaney, Maggie; Bellefeuille, Gerard (Advances in Social Sciences Research Journal, 2024)
This article has been written as a bridge for instructors who want to move away from conventional teaching methods but are unsure of how to do so. It profiles a relational ontological approach to teaching and learning and an arts-based theoretical framework learning assessment that child and youth care (CYC) complete for an advanced undergraduate third year CYC practice methods course. The advance methods practice course has as its focus the integration of theory, self, and ethical practice. It argues that creative experiential arts-based methods tap directly into the human experience by inviting students to attend to alternative ways of knowing and sense-making, thereby facilitating richer and deeper learning experiences by bringing to consciousness the spiritual, emotional, and mythological aspects of the self, which offers students new landscapes of reflection on themselves, their studies, and their views of the world.